The Effect of the War on the Marine Fishing and Fish Consumption in the Governorate of Latakia - وزّان كنده (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
Latakia governorate is the main producer of marine fishes in Syria. The war in the country has affected this sector which is the only source of marine fishes. This study assess the decrease of annual production volume and the decline of individual consumption due to the high cost of living, this is before and during the war under a considering period (2006-2017-20). The study showed that the average of volume production during the war has reduced by 56%, the compound annual growth rate was negative in both period (-2.3% and -2.7% respectively), the simple linear regression equation showed that the product volume has decreased before war by -80 tonnes per year equal to 3.1% of average, while it decreased by -54.4 tonnes, equal to 3.3 % of average during the war. The per capita of available fish consumption has declined by 59% (from 1.8 to 0.72 kg). The IN price has increased to 1406.6%. The study recommended the necessity to stop the war, to depend more on local economic factors in order to stimulate the national economy, and to start investing in fish farming as a new sources of marines fishes.